Perbedaan metode konseling ceramah keluarga berencana terhadap pengetahuan tentang kontrasepsi rasional pada akseptor premenopause di Puskesmas Cangkringan - Fitri Nurdjanah; Heni Puji Wahyuningsih; Nining Wiyati (Poltekkes Kemenkes Yogyakarta, 2012)
BKKBN reporting March 2011 known that injectable contraceptive use in Indonesia reached 47.71%,45.74% DIY, Sleman 48.69% and 57.36% in the Cangkingan Public Health Center, this does not fit the guidelines use of rational contraceptives even more to the premenopausal acceptor in Cangkingan Public Health Center reached 90%. Contraceptives selection behavior one influenced by the level of knowledge where itself knowledge can be through the lecture method and family planning counseling. Objectives: to knowing different family planning counseling of method and lectures on knowledge of rational contraception in premenopausal acceptor at the Cangkingan Public Health Center 2011. Methods: this type of Quasy experiment study pretest-posttest group design and static comparison group design. The formula samples large using for two independent groups and obtained of 72 respondents who are premenopausal acceptor at the Cangkingan Public Health Center. That instrument study has been using a questionnaire tested validity and reliability. Analysis of test data using dependent t-test and independent t-test with SPSS software for Windows. Results : by dependent t-test from lectures of method knowledge results obtained t count (15,707) > t table (1,684) and p-value (0.000) <0.05,counseling of method (13,643) > t table (1,684) and p-value (0,000) < 0,05. By independent t-test knowledge results obtained count (3.138)> table (1.684) and p-value (0.002) <0.05.